2019
DOI: 10.1094/pdis-03-19-0531-re
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Assay Allows the Simultaneous Detection of 12 Fungi Causing Fruit Rot in Cranberry

Abstract: Cranberry fruit rot (CFR) is arguably one of the most limiting factors of cranberry (Vaccinium macrocarpon) production throughout its growing areas. The disease is caused by a group of closely related fungi that require identification using long and cumbersome steps of isolation and microscopic observations of structural features. The objective of this study was to develop a molecular assay to simultaneously detect and discriminate 12 of the most important fungal species reported to be pathogenic on cranberry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In recent years, molecular techniques have revolutionized and greatly facilitated the diagnostic of plant pathogens (Kostov et al ., ; Michalecka et al ., ; Reich et al ., ; Silva et al ., ; Burbank and Ortega, ). Among other applications, they have allowed the precise identification of the causal agents of diseases caused by a complex of fungi (Conti et al ., ), the fulfillment of Koch's postulates with closely related species such as Fusarium spp. (Moine et al ., ), and the diagnosis of the presence and identity of a pathogen from levels that were hitherto undetectable (Rollins et al ., ; Haudenshield et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, molecular techniques have revolutionized and greatly facilitated the diagnostic of plant pathogens (Kostov et al ., ; Michalecka et al ., ; Reich et al ., ; Silva et al ., ; Burbank and Ortega, ). Among other applications, they have allowed the precise identification of the causal agents of diseases caused by a complex of fungi (Conti et al ., ), the fulfillment of Koch's postulates with closely related species such as Fusarium spp. (Moine et al ., ), and the diagnosis of the presence and identity of a pathogen from levels that were hitherto undetectable (Rollins et al ., ; Haudenshield et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…vaccinii has been carried out by the isolation approach followed by morphological screening and sequencing or using an end-point PCR assay (Conti et al, 2019). In the present study, a new TaqMan probebased real-time PCR assay was developed for specific and sensitive detection of D. vaccinii targeting the TEF1 gene region.…”
Section: Discussionmentioning
confidence: 99%
“…A rapid increase in the movement of plant material worldwide has increased the need for rapid and efficient monitoring of imported plant material for unwanted plant pathogens. To date, the detection of D. vaccinii has been carried out by the isolation approach followed by morphological screening and sequencing or using an end‐point PCR assay (Conti et al, 2019). In the present study, a new TaqMan probe‐based real‐time PCR assay was developed for specific and sensitive detection of D. vaccinii targeting the TEF1 gene region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The designated primers successfully amplified a 400 bp fragment from F. buharicum genomic DNA, allowing for the discrimination of F. buharicum from other fungal species. Several species-specific primers, utilizing this gene, have been developed and employed for detecting various plant pathogenic fungi, including Fusarium [10,[31][32][33]. The primer developed in this study demonstrated high specificity for F. buharicum and sensitivity, capable of detecting the pathogen at concentrations as low as 1.0 ng of fungal genomic DNA in conventional PCR assays.…”
Section: Plos Onementioning
confidence: 99%